Hadiste akran rivayeti - Sever Arslan, Hatice (My University, 2025)
Hadiste akran rivayeti Bu çalışma, bir hadis usûlü konusu olan akran rivâyetini ayrıntılı olarak incelemektedir. Konu, rivâyetü’l-akrân ve müdebbec olmak üzere iki alt başlıkta ele alınmıştır. Akran olan râvîlerin birinin diğerinden tek taraflı rivâyetine rivâyetü’l-akrân, birbirinden karşılıklı rivâyetine ise müdebbec denir. Türkçe literatürde akran rivâyeti üzerine kapsamlı bir çalışma bulunmadığından konunun ayrıntılı bir biçimde ele alınması hedeflenmiştir. Çalışmanın ilk bölümünde rivâyetü’l-akrân ve müdebbecin tanımına, ilişkili bir terim olan rivâyetü’l-ekâbir ani’l-esâgir’in tanımına yer verilmiş; bu terimlerin birbirinden farklılıkları ortaya konmuştur. Ardından akran rivâyetinin önemine, sebeplerine ve konuyla ilgili yapılan çalışmalar sunulmuştur. Hadis rivâyet geleneğinde asıl olan, senedin mümkün olduğunca kısa tutulduğu ve her tabakadan tek bir râvînin yer aldığı bir rivâyet zinciri ile metne ulaşmasıdır. Akran rivâyetinde ise durum farklıdır. Zira aynı tabakadan bir veya birden fazla akranın olması senedi uzatır. Bu nedenle akla ilk olarak aynı tabakadaki iki veya daha fazla râvînin birbirinden hadis rivâyet etmesi gelmez. Ayrıca bu durum, aynı hocadan hadis dinlemiş iki veya daha fazla râvî olduğu yanılgısına da sebep olabilir. Hadisteki akran rivâyetlerinin bilinmesi, senedde “vav” yerine “an” konduğu ya da yanlışlıkla senede ilave râvi eklendiği gibi yanlış yargılara düşmeyi önler. Kavramın ne zamandan itibaren hadis usûlüne dâhil edildiğine bakıldığında dördüncü asırdan itibaren kullanılmaya başlandığı görülür. Nitekim Zeynüddin el-Irâki (ö. 806/ 1404), müdebbec terimini ilk defa kullanan kişinin Dârekûtnî (ö. 385/ 995) olduğunu söylemiştir. Müellifin bu konuda el-Müdebbec isimli müstakil bir eseri bulunmakla beraber bu kitap günümüze ulaşmamıştır. Çalışmamızın ikinci bölümünde ise usûl kitaplarında geçen rivâyetü’l-akran ve müdebbec örnekleri incelenmiş ve neticede akran rivâyetinin, rivâyetü’l-ekâbir ani’l-esâgir teriminden farklı olduğu sonucuna varılmıştır.

Narrating hadith from peers This study provides a detailed examination of peer narration, a subject within the science of hadith methodology. The topic is addressed under two subheadings: rivāyet al-akrān and mudebbec. The unilateral narration of one peer narrator from another is termed rivāyet al-akrān, whereas their mutual narration from one another is called mudebbec. As there is no comprehensive study on peer narration in the Turkish literature, this work aims to address this subject in detail. The first section of the study presents the definitions of rivāyet al-akrān, and mudebbec, along with the definition of a related term, rivāyet al-ekābir an al-esāgir, and delineates the distinctions between these concepts. Subsequently, the importance and reasons for the occurrence of peer narration, as well as previous scholarly work on the topic, are discussed. In the tradition of hadith transmission, the ideal is to reach the text through an isnād that is as short as possible, featuring only a single narrator from each generation. The case is different with peer narration, as the presence of one or multiple peers from the same generation lengthens the isnād. Consequently, the scenario of two or more contemporary narrators transmitting from one another is not the primary assumption. Furthermore, this situation can lead to the erroneous conclusion that there were multiple narrators who directly heard the hadith from the same teacher. Knowledge of peer narrations prevents one from falling into erroneous judgments, such as mistaking the particle an for “vav” in a chain of transmission, or incorrectly assuming an additional narrator was added to the chain. An examination of when the concept was incorporated into hadith methodology reveals that its usage began from the fourth Islamic century. Indeed, Zayn al-Dīn al-ʿIrāqī (d. 806/ 1404) stated that al-Dāraqutnī (d. 385/ 995) was the first to employ the term mudebbec. Although the author composed an independent work on this subject titled al-Mudabbec, this book has not survived to the present day. In the second section of our study, examples of rivāyet al-akrān and mudebbec found in classical works of hadith methodology are analyzed, leading to the conclusion that peer narration is distinct from the term rivāyet al-ekābir an al-esāgir.
Narrating hadith from peers
Keywords: Akran; Hadis; Hadis Mudebbec; Hadith; Müdebbec; Narration; Peer; Rivayet; Rivāyet al-Akrān; Rivâyetü’l-Akrân